Effects of Using Command and Reciprocal Teaching on Skill Achievement of Students of Gymnastics Course at School of Sports Sciences at University of Jordan - Jad Mazahreh; Ghazi Kilani (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives:  This study aims to identify the effect of using command and reciprocal styles on achievement of students studying gymnastics at School of Sports Sciences at the University of Jordan. Methods: The researcher used a quasi-experimental approach.  The sample of the study consisted of (42) male students from Gymnastics (1) course.  Two sections were selected intentionally. The first section (the control group) consisted of (19) male students who learned through a command style. The second section (the experimental group) consisted of (23) male students who learned through a reciprocal style. Results: The results of the study showed a positive effect for the reciprocal style on skill achievement students. Conclusions: The researcher recommends diversifying teaching strategies during lectures of gymnastics at the University of Jordan, especially by including reciprocal learning style in teaching gymnastic skills to students as it proved to be effective in building the skills of students compared to the command style method.